How should donors manage adaptively? Market Systems Development as a case study. - Itad (Itad, 2018)
Itad has recently completed a strategic evaluation for Sida to help them work through how they can best manage programmes that are adaptive and apply systems approaches - the conclusions from the evaluation about what funders need to do to manage adaptively are of broader relevance.

Managing to Adapt: Analysing adaptive management for planning, monitoring, evaluation, and learning - Desai, Harsh; Maneo, Gabriele; Pellfolk, Erica; Schlingheider, Annika (Oxfam Research Reports, 2018)
Adaptive management is at the heart of ‘Doing Development Differently’. It emerges from stakeholders’ calls for development programmes to be more flexible and responsive to their contexts. Whether it becomes a mainstreamed practice depends on how much it is

Procuring and Managing Adaptively: 5 Case Studies of Adaptive Mechanisms - Pryor, Tony (USAID Learning Lab, USAID, 2018)
Flexibility in program management is essential in all of the countries where USAID works. This is especially true in non-permissive environments (NPEs), where the ability to learn and adapt quickly to changing circumstances can help USAID staff members achieve their desired outcomes.

The relationship between adaptive management of social-ecological systems and law: a systematic review - Frohlich, Miguel F.; Jacobson, Chris; Fidelman, Pedro; Smith, Timothy F. (Ecology and Society, 2018)
Adaptive management has been considered a valuable approach for managing social-ecological systems involving high levels of complexity and uncertainty. However, many obstacles still hamper its implementation. Law is often seen as a barrier for moving adaptive management beyond theory, although there has been no synthesis on the challenges of legal constraints or how to overcome them. We contribute to filling this knowledge gap by providing a systematic review of the peer-reviewed literature on the relationship between adaptive management and law in relation to social-ecological systems. We analyze how the scholarship defines the concept of adaptive management, identifies the legal barriers to adaptive management, and the legal strategies suggested for enabling this approach. Research efforts in this domain are still highly geographically concentrated in the United States of America, unveiling gaps concerning the analysis of other legal jurisdictions. Overall, our results show that more flexible legal frameworks can allow for adaptive management without undermining the role of law in providing stability to social interactions. Achieving this balance will likely require the reform of existing laws, regulations, and other legal instruments. Legal reforms can facilitate the emergence of adaptive governance, with the potential to support not only adaptive management implementation but also to make law itself more adaptive.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Pyoe Pin, Myanmar - Christie, Angela; Green, Duncan (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches in aid programming in a fragile, conflict and violence-affected setting (FCVAS), namely Myanmar. A combination of desk review and field research has been used to examine some of the assertions around the ‘adaptive management’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blue-print and linear project plans. This paper explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for promoting empowerment and accountability in such ‘messy places’. This case study focuses on Pyoe Pin (‘Young Shoots’), a DFID-funded, British Council managed governance programme, which has been running since 2007.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Adapting to Learn and Learning to Adapt: Practical Insights from International Development Projects - Brinkerhoff, Derick W.; Frazer, Sarah; McGregor, Lisa (RTI Press, 2018)
Adaptive programming and management principles focused on learning, experimentation, and evidence-based decision making are gaining traction with donor agencies and implementing partners in international development. Adaptation calls for using learning to inform adjustments during project implementation. This requires information gathering methods that promote reflection, learning, and adaption, beyond reporting on pre-specified data. A focus on adaptation changes traditional thinking about program cycle. It both erases the boundaries between design, implementation, and evaluation and reframes thinking to consider the complexity of development problems and nonlinear change pathways.Supportive management structures and processes are crucial for fostering adaptive management. Implementers and donors are experimenting with how procurement, contracting, work planning, and reporting can be modified to foster adaptive programming. Well-designed monitoring, evaluation, and learning systems can go beyond meeting accountability and reporting requirements to produce data and learning for evidence-based decision making and adaptive management. It is important to continue experimenting and learning to integrate adaptive programming and management into the operational policies and practices of donor agencies, country partners, and implementers. We need to devote ongoing effort to build the evidence base for the contributions of adaptive management to achieving international development results.

Portfolios of Agile Projects: A Complex Adaptive Systems’ Agent Perspective - Sweetman, Roger; Conboy, Kieran (Project Management Journal, 2018)
While agile approaches can be extremely effective at a project level, they can impose significant complexity and a need for adaptiveness at the project portfolio level. While this has proven to be highly problematic, there is little research on how to manage a set of agile projects at the project portfolio level. What limited research that does exist often assumes that portfolio-level agility can be achieved by simply scaling project level agile approaches such as Scrum. This study uses a complex adaptive systems lens, focusing specifically on the properties of projects as agents in a complex adaptive portfolio to critically appraise current thinking on portfolio management in an agile context. We then draw on a set of 30 expert interviews to develop 16 complex adaptive systems (CAS)-based propositions as to how portfolios of agile projects can be managed effectively. We also outline an agenda for future research and discuss the differences between a CAS-based approach to portfolio management and traditional approaches.

In pursuit of the deep and sustained shifts necessary for adaptive management - Simister, Nigel (INTRAC, 2018)
The final blog in Nigel Simister's series on adaptive management and the M&E of complex projects and programmes.

How Adaptive Management is challenging the monitoring and evaluation of complex programmes - Simister, Nigel (INTRAC, 2018)
By Nigel Simister Adaptive management is a broad approach designed to support development or humanitarian programmes in complex or uncertain …

Connect. Learn. Adapt. Repeat - Practicing adaptive management in complex, conflict-affected environments: barriers and promising practices - Queen, Emily Forsyth (2018)
To shift aid culture toward adaptive management, we can: - Stay humble, empathetic, and build skills in facilitation and listening. - Focus on working with more flexible foundations or individual donors. Or, work for more rigid donors and help make their policies more flexible. - Get clearer about goals and processes while finding ways to be less specific and more committed to local leadership about pathways to get to the goal. - Resist looking for a magic adaptive management tool and instead get clearer about when teams make what kinds of decisions and matching to tools that support that decision-making. - Validate that everyone’s perspective is a form of data and try out simple ways to document how teams learns and changes. - Broaden and ground the idea of expertise – remembering that, especially when working with folx on the margins, people are the only experts on their own life. Practitioners must also examine how dominant patriarchal, white supremacist, colonial ideas have pushed us toward wanting more control, less flexibility, and less space for equitable decision making.

Learning to make a difference: Christian Aid Ireland’s adaptive programme management in governance, gender, peace building and human rights - Booth, David; Balfe, Karol; Gallagher, Róisín; Kilcullen, Gráinne; O'Boyle, Sarah; Tiernan, Alix (ODI, 2018)
This paper assesses the relevance of adaptive or trial-and-error approaches to the field of governance, peace building and human rights. Tackling the problems of poverty, vulnerability and exclusion that persist in parts of the world that continue to be affected by violence or political insecurity is difficult for several reasons. For one, because of the complexity of the prevailing social, economic and political systems, solutions to chronic problems are far from obvious. One response to this aspect of the challenge is adaptive programme design and management. This paper is the product of a multi-year collaboration between ODI and the core team of Christian Aid Ireland to assess the relevance of adaptive or trial-and-error approaches to the field of governance, peace building and human rights. It explains the basis on which Christian Aid Ireland’s current five-year programme has become committed to an adaptive approach. It then describes and seeks to draw lessons from the programme’s first year of experience, considering the possible implications for implementation over the coming years. The authors find that to get full benefits from the move to adaptive management, the new ways of working and their underlying principles will need to become more embedded in organisational practices and cultures.

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume I: Evaluation Report - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Evaluation of the market systems development approach, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume II: Case studies - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Evaluation of the market systems development approach, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Program Cycle - Discussion Note: Adaptive Management - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Simplicity, Accountability and Relationships: Three ways to ensure MEL supports Adaptive Management - Roche, Chris (From Poverty to Power, 2018)
Based on a recent discussion in Manila, Chris Roche reflects on how Monitoring, Evaluation and Learning can better support 'adaptive programming'.

Program Cycle - Discussion Note: Managing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

OPM’s approach to assessing Value for Money - King, Julian; OPM (Oxford Policy Management, 2018)
This document offers practical guidance for assessing value for money (VfM) in international development programmes. Since 2016, evaluation expert Julian King has been working with OPM to develop and deploy a robust approach to VfM assessment. The approach combines cutting-edge evaluation practice with concepts from economic evaluation to respond to donor requirements for accountability and good resource allocation, as well as to support reflection, learning, and adaptive management.

Doing Development Differently at Scale - Pellini, Arnaldo; Karetji, Petrarca C.; Soekadis, Ade (Knowledge, Politics and Policymaking in Indonesia, 2018)
In recent decades there has been an increasing recognition that politics and political institutions matter for development. There is also a much greater interest in contextually grounded approaches. This has stemmed from an acknowledgement that purely technocratic approaches to development often result in failure because they do not take into account the nature of political institutions. Nor do they take account of the context in a particular developing country and the interests and incentives of powerful national actors. Policy processes are embedded in specific social, political and organisational contexts. Approaches that focus on implementing universal best practices in evidence-informed policymaking are unlikely to be successful. Instead, what is needed is an approach that takes the local context as the starting point for understanding what issues are relevant to policymakers and developing contextually appropriate solutions. The authors of this chapter reflect on the management approaches and systems that may be required to enable and support large-scale development programmes to be flexible and adaptive to the local policy context and circumstances. The chapter argues that such programmes struggle to adopt adaptive management principle and that to do that at scale requires some changes in the way such programmes are managed.
Keywords: Adaptive Management; Doing development differently; Evidence-informed policymaking; Indonesia; Knowledge sector; Thinking and working politically

Adaptive Peacebuilding Programming Through Effective Feedback Loops: Promising Practices - Barnard-Webster, Kiely; Jean, Isabella (CDA, 2018)
This case study report was developed by CDA’s part of Peacebuilding Evaluation Consortium collaborative research on the use of feedback loops in support of adaptive programming. Feedback loops are just one element of adaptive programming and are defined and used in different ways by organizations working on social change, peace and development issues. This document includes key findings from our desk review of reports and grey literature, key informant interviews, observations documented during CDA’s advisory and learning engagements with peacebuilding partners as well as the case study on SFCG’s feedback processes in Burundi. The findings are most relevant to program and M&E staff but have implications for senior management and policymakers in light of growing interest in strengthening adaptive management.

Snapshot of Adaptive Management in Peacebuilding Programs - Queen, Emily Forsyth; Baumgardner-Zuzik, Jessica; Hume, Elizabeth; Greenberg, Melanie (Alliance for Peacebuilding, 2018)
The Alliance for Peacebuilding developed the report Snapshot of Adaptive Management in Peacebuilding Programs with support from Humanity United. This report examines how existing organizational programs are designing and learning from adaptive management in a conflict effected and fragile states. It further provides practical recommendations for applying adaptive management to peacebuilding programs based on synthesis … Continue reading "Snapshot of Adaptive Management in Peacebuilding Programs"
Keywords: KEY

Adaptive management: why we find it so hard to operationalise - Teskey, Graham (Abt Associates - Governance Soapbox, 2018)

Building a global learning alliance on adaptive management - Wild, Leni; Ramalingam, Ben (ODI, 2018)

Iterative Design and Monitoring for Adaptive Management: How Causal Link Monitoring can help - Britt, Heather; Hummelbrunner, Richard; Green, Jackie (Better Evaluation, 2018)
Development actors are embracing the concept and practice of adaptive management, using evidence to inform ongoing revisions throughout implementation. In this guest blog, Heather Britt, Richard Hummelbrunner and Jackie Greene discuss a practical approach that donors and partners can use to agree on what’s most important to monitor as a project continues to evolve.

Summer School Course - Adaptive Management - Working Effectively in the Complexity of International Development (weekplan) - Green, Duncan; Guijt, Irene (Oxfam, 2018)

Walking the adaptive talk - Denney, Lisa (Devpolicy Blog from the Development Policy Centre, 2018)
The first in a three-part series on adaptive aid.Lisa Denney clarifies the confusion.

DFID’s approach to value for money in programme and portfolio management - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
ICAI published this review on DFID’s approach to value for money in February 2018, and as value for money is both a process and an outcome and cuts across all aspects of DFID’s operations, did not score this review. We made five recommendations and published a follow-up to this review in July 2019. All UK government departments are required to achieve value for money in their use of public funds. In recent years, DFID has been working to build value for money considerations further into its management processes and its relationships with implementers and multilateral partners, establishing itself as a global champion on value for money. Review This review was published in February. Though it was not rated, ICAI made five recommendations, and found that the Department for International Development’s approach to value for money was helping to make UK aid spending go further, but improvements are still needed. Findings This review found that DFID has strengthened its processes and systems for ensuring it gains maximum value for each pound spent, has taken swift remedial action to tackle under-performing programmes, and has become a strong global champion on value for money. The review also found that DFID has been diligent in its efforts to cut waste, detect fraud, and improve efficiency, and that this work is improving the return on the UK investment in aid. However, the review found that DFID’s approach was not adequately reporting and capturing results and value for money at the country portfolio level, or how programmes work together to deliver lasting impact, including reducing future dependency on aid. It also found that weakness in the annual review process could undermine DFID’s approach to value for money. It found that targets were frequently revised, and that there could be pressures for optimistic scoring of programmes. Recommendations Based on this review, we made the following five recommendations to help DFID improve its approach to value for money still further: DFID country offices should articulate cross-cutting value for money objectives at the country portfolio level, and should report periodically on progress at that level. Drawing on its experience with introducing adaptive programming, DFID should encourage programmes to experiment with different ways of delivering results more cost-effectively, particularly for more complex programming. DFID should ensure that principles of development effectiveness – such as ensuring partner country leadership, building national capacity and empowering beneficiaries – are more explicit in its value for money approach. Programmes should reflect these principles in their value for money frameworks, and where appropriate incorporate qualitative indicators of progress at that level. DFID should be more explicit about the assumptions underlying the economic case in its business cases, and ensure that these are taken into account in programme monitoring. Delivery plans should specify points in the programme cycle when the economic case should be fully reassessed. Senior responsible owners should also determine whether a reassessment is needed following material changes in the programme, results targets or context. Annual review scores should include an assessment of whether programmes are likely to achieve their intended outcomes in a cost-effective way. DFID should consider introducing further quality assurance into the setting and adjustment of logframe targets.

Monitoring and evaluation for adaptive programming - Roche, Chris; Kelly, Linda (Devpolicy Blog from the Development Policy Centre, 2018)
Chris Roche and Linda Kelly with six take-aways on what is being tried and learnt in setting up monitoring and evaluation frameworks for adaptive programs.

Old Wine in New Bottles? 6 ways to tell if a programme is really ‘doing development differently’ - Green, Duncan (From Poverty to Power, 2018)
Some top adaptive management exponents give their top tips on how to distinguish spin from reality, when looking at an avowedly AM programme

Program Cycle - Discussion Note: Designing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Navigation by Judgment: Why and when Top Down Management of Foreign Aid Doesn't Work - Honig, Dan (Oxford University Press, 2018)
Foreign aid organizations collectively spend hundreds of billions of dollars annually, with mixed results. Part of the problem in these endeavors lies in their execution. When should foreign aid organizations empower actors on the front lines of delivery to guide aid interventions, and when should distant headquarters lead? In Navigation by Judgment, Dan Honig argues that high-quality implementation of foreign aid programs often requires contextual information that cannot be seen by those in distant headquarters. Tight controls and a focus on reaching pre-set measurable targets often prevent front-line workers from using skill, local knowledge, and creativity to solve problems in ways that maximize the impact of foreign aid. Drawing on a novel database of over 14,000 discrete development projects across nine aid agencies and eight paired case studies of development projects, Honig concludes that aid agencies will often benefit from giving field agents the authority to use their own judgments to guide aid delivery. This "navigation by judgment" is particularly valuable when environments are unpredictable and when accomplishing an aid program's goals is hard to accurately measure. Highlighting a crucial obstacle for effective global aid, Navigation by Judgment shows that the management of aid projects matters for aid effectiveness.

DRG Center practical tips to implement more context-adaptive programming - Jacobstein, David (#AdaptDev, 2018)
Hi #adaptdevers, The cross-sectoral programs team in the DRG Center have been working in support of ways that programming can be made more aware of, and responsive to, context considerations that have to do with incentives and relationships between different actors - often called power dynamics or political economy. Following several discussions with field folks, we were asked to come up with simple and practical tips that could help staff to implement more context-adaptive programming, or to better Work Politically to use TWP jargon. With assistance from many of our field staff and partners, we've put together three documents (to start) that have now been cleared to share publicly: • Tips on Making Your Solicitations Invite Context-Driven Adaptive Programming - suggestions spanning most sections of a typical solicitation to better weave in Thinking and Working Politically. I'm particularly excited that this document contains embedded links to excerpts from a set of solicitations that model good practice. You can also find a summary of all the excerpts from real solicitations, and links onward to the public posting of those solicitations on Fed Biz Ops or Grants.gov, here. • Tips on Power Dynamics and Theories of Change - suggestions relevant to those working on project designs and logic models. • Tips for Better Use of Advisory Councils - suggestions to set up better advisory bodies that help you to incorporate political economy more automatically into your programmatic adjustments. I hope that you'll find these practical and helpful! Feedback is always welcome. Best, David

Evaluation and learning in complex, rapidly changing health systems: China’s management of health sector reform - Xiao, Yue; Husain, Lewis; Bloom, Gerald (Globalization and Health, 2018)
Healthcare systems are increasingly recognised as complex, in which a range of non-linear and emergent behaviours occur. China’s healthcare system is no exception. The hugeness of China, and the variation in conditions in different jurisdictions present very substantial challenges to reformers, and militate against adopting one-size-fits-all policy solutions. As a consequence, approaches to change management in China have frequently emphasised the importance of sub-national experimentation, innovation, and learning. Multiple mechanisms exist within the government structure to allow and encourage flexible implementation of policies, and tailoring of reforms to context. These limit the risk of large-scale policy failures and play a role in exploring new reform directions and potentially systemically-useful practices. They have helped in managing the huge transition that China has undergone from the 1970s onwards. China has historically made use of a number of mechanisms to encourage learning from innovative and emergent policy practices. Policy evaluation is increasingly becoming a tool used to probe emergent practices and inform iterative policy making/refining. This paper examines the case of a central policy research institute whose mandate includes evaluating reforms and providing feedback to the health ministry. Evaluation approaches being used are evolving as Chinese research agencies become increasingly professionalised, and in response to the increasing complexity of reforms. The paper argues that learning from widespread innovation and experimentation is challenging, but necessary for stewardship of large, and rapidly-changing systems.

Timely evaluation in international development - Webster, Jayne; Exley, Josephine; Copestake, James; Davies, Rick; Hargreaves, James (Journal of Development Effectiveness, 2018)
Impact and process evaluations are increasingly used in international development; however they are generally retrospective in outlook. A more timely approach to evaluation aims to identify necessary, feasible and effective changes during a programme or intervention’s lifetime. This paper aims to identify, categorise, describe and critically appraise methods to support more timely evaluation in international development. Potential methods were identified through scoping seminar, public symposium, targeted review of the literature, and the authors’ own experiences and opinions. Findings from the different data sources were reviewed collectively by the author group and triangulated to develop an analytical framework. We identified four purposes of timely evaluation for international development, and critiqued the use of approaches against four dimensions of timeliness and flexibility. Whilst we found significant interest in more timely approaches to evaluation in international development, there was a dearth of published empirical evidence upon which to base strong recommendations. There is significant potential for timely evaluation to improve international development outcomes. New approaches to mixing and adapting existing methods, together with new technologies offer increased potential. Research is needed to provide an empirical evidence base upon which to further develop the application, across sectors and contexts, of timely evaluation in international development.
Keywords: Adaptive learning; Outcome evaluation; Programme improvement; impact evaluation

Discussion Note: Complexity-Aware Monitoring - USAID (Program Cycle, 2018)
This Discussion Note complements ADS 201 and outlines general principles and promising approaches for monitoring complex aspects of USAID development assistance. Complexity-aware monitoring is a type of complementary monitoring that is useful when results are difficult to predict due to dynamic contexts or unclear cause and-effect relationships. Key principles of the Program Cycle include applying analytic rigor, managing adaptively, and utilizing a range of approaches to achieve results. ADS 201.3.5.5 identifies three types of program monitoring – performance, context, and complementary. All USAID programming incorporates performance monitoring and should include context monitoring. Performance monitoring “is the ongoing and systematic collection of performance indicator data and other quantitative or qualitative information to reveal whether implementation is on track and whether expected results are being achieved.” Context monitoring is “[t]he systematic collection of information about conditions and external factors relevant to the implementation and performance of an operating units (OU’s) strategy, projects, and activities.” As stated in ADS 201.3.5.5, complementary monitoring may be used by missions and Washington OUs to complement performance and context monitoring in situations where results are difficult to predict due to dynamic contexts or unclear cause-andeffect relationships. This Discussion Note provides an explanation of when to use complementary monitoring approaches that are complexity-aware and summarizes the three principles of complexity-aware monitoring.

Integrating Food Security and Wild Caught Fisheries Management in USAID Programming. Illustrative situation Model and Results Chain - Swaminathan, Vinaya; Best, Barbara; Ajroud, Brittany (Measuring Impact, 2018)
Integrating Food Security and Wild Caught Fisheries Management in USAID Programming is an illustrative case example that demonstrates how two adaptive management programming tools—situation models and results chains—can help USAID staff and its partners to better design and implement activities that integrate food security, nutrition, and sustainable management of wild fisheries.

MLE or MEL in adaptive programming? - Pellini, Arnaldo (Knowledge counts, 2018)

Using adaptive monitoring, evaluation and learning in programme design - Nzegwu, Femi (INASP, 2018)

The role of research and learning in adaptive programming - Babon, Andrea; Denney, Lisa (Devpolicy Blog from the Development Policy Centre, 2018)
Andrea Babon and Lisa Denney explore how learning partners - a common feature of aid programs - can operate and feed into programs.

Achieving value for money through procurement. Part 2: DFID’s approach to value for money through tendering and contract management - A performance review - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
Summary In 2016-17, the Department for International Development (DFID) spent £1.4 billion, or 14% of its budget, through commercial suppliers on contracts ranging from school construction to family planning services and the delivery of humanitarian aid. The quality of its procurement and contract management – how it engages and manages commercial firms to support the delivery of aid programmes on time, to budget and at the appropriate quality – is a key driver of value for money for UK aid. It is also a subject of considerable Parliamentary and public interest. In recent years, DFID has implemented a range of initiatives to strengthen its procurement practices and embed commercial capability across the department – including its 2017 Supplier Review, undertaken to address concerns about excessive profit-making by DFID suppliers. This review on achieving value for money through procurement (part 2) was published in September 2018. We awarded a green-amber score and made three recommendations to government. The follow-up to this review was published in July 2020, and rated the government’s response as ‘inadequate’, as a result of DFID’s failure to put in place a formal contract management regime, despite the risks this entails for programme results. We will return to this in the next follow-up in summer 2021. Review Our review found an appropriate overall approach to procurement with good performance in most areas of tendering, but significant weaknesses in contract management. We therefore awarded a green-amber score and made three recommendations to government. Findings Since 2015, DFID has progressed towards a more mature procurement approach. DFID’s tender process follows current EU legislation and UK government guidelines and cross-government peer reviews confirm improvements in DFID’s procurement approach. The Supplier Review lent momentum to the reforms but risks having unintended consequences. Poor consultation with suppliers has heightened the risk of unintended consequences. DFID is reviewing its business processes to protect aid recipients from sexual abuse and exploitation. DFID does not always choose the most appropriate procurement process but a new strategic sourcing process has resulted in stronger procurement planning. DFID has built up its commercial capability, but this will need to be an ongoing process. The contract management function in DFID is poorly defined and contracts are frequently amended or extended beyond their advertised length and values. Inception phases are often too short for adequate preparation and planning. Progress on flexible and adaptive programming will require more innovative approaches to tendering and contract management. Recommendations Before the next major revision of its supplier code and contracting terms, or future changes that may materially affect suppliers, DFID should conduct an effective consultation process with its supplier market, to ensure informed decisions and minimise the risks of unintended consequences. DFID should accelerate its timetable for acquiring a suitable management information system for procurement, to ensure that its commercial decisions are informed by data. DFID should instigate a formal contract management regime, underpinned by appropriate training and guidance and supported by a senior official responsible for contract management across the department. The new regime should include appropriate adaptive contract management techniques, to ensure that supplier accountability is balanced with the need for innovation and adaptive management in pursuit of development results.

Course: Introduction to Collaborating, Learning and Adapting (CLA) in the Program Cycle - USAID LEARN (USAID Learning Lab, 2018)

Dynamic gridlock: Adaptive Humanitarian Action in the Democratic Republic of Congo - Obrecht, Alice (ALNAP Country Study, 2018)

Sample criteria to select case studies for evaluation - Methods Lab (2018)
Time and budget constraints often mean that organisations are unable to evaluate all of their programmes, and large programmes, operating in multiple locations, are unable to evaluate all project sites. This tool introduces two sets of criteria to support evaluators and programme managers to select case studies or programmes for evaluation: i) information about how relevant or feasible evaluation is for individual programmes, and ii) across the overall portfolio, strategic thinking around what types of cases are most important to understand. This tool was developed by Anne Buffardi, Irene Guijt, Simon Hearn and Tiina Pasanen for use in The Methods Lab projects.

Decision-Making and Data Use Landscaping [at DFID] - Powell, Josh; Orton-Vipond, Sarah; Bhatia, Vinisha; Kilroy, Annie (Development Gateway, 2018)
As DFID aims to harness the Data Revolution, ensuring that data1 drive decision-making, public accountability, and the achievement of the Sustainable Development Goals (SDGs), ensuring that systems, processes, and skills for data are aligned with these objectives is paramount. Across sector policy teams, country offices, and various analytical and technical cadres, different strengths and weaknesses, as well as needs and ambitions exist. To inform a strategic approach to data, as framed in its forthcoming Data Roadmap, DFID collaborated with Development Gateway to perform a Decision and Data Use Landscaping study. This report details lessons learned from approximately 60 interviews across 4 DFID country offices, all sector policy teams, senior managers, and various analytical and technical cadres and offices.

MIRADI: Adaptive Management Software for Conservation Projects (2018)

Global governance and local peace: accountability and performance in international peacebuilding - Campbell, Susanna (Cambridge University Press, 2018)
Local peacebuilding and global accountability -- The country context--Burundi from 1999 to 2014 -- Ingos in peacebuilding--globally unaccountable, locally adaptive -- International organizations in peacebuilding--globally accountable, locally constrained -- Bilateral development donors--accountable for global targets, not local change

Guidance: Rigor and Reproducibility in Grant Applications | grants.nih.gov - NIH (National Institutes of Health, 2018)

Sounding clever or being smart? – How to do more with less in evaluating governance programmes - Aston, Tom (Care Insights, 2018)
About a decade ago, the development sector fell into the same trap the financial services industry did in the mid-1990s. We were all seduced by clever...

Q&A: Complexity-Aware Planning for Stabilization Programming - Martins, Christy (DAI - Checkpoint, 2018)

Combining Big Data and Thick Data to Improve Services Delivery - Ang, Yuen Yuen (IBM Center for The Business of Government, 2018)

The Global Wildlife Program - Knowledge Platform - 2016-2018 - WB (The World Bank, 2018)

Evidence to Action: Research to Address Illegal Wildlife Trade - Milner-Gulland, E. J.; Cugniere, Laure; Hinsley, Amy; Phelps, Jacob; Rolfe, Michael 't Sas; Veríssimo, Diogo (2018)
Tools and expertise to improve the evidence base for national and international Illegal Wildlife Trade policy already exist but are underutilised. Tapping into these resources would produce substantive benefits for wildlife conservation and associated sectors, enabling governments to better meet their obligations under the Sustainable Development Goals and international biodiversity conventions. This can be achieved through enhanced funding support for inter-sectoral research collaborations, engaging researchers in priority setting and programme design, increasing developing country research capacity and engaging researchers and community voices in policy processes. This briefing, addressed to policy makers and practitioners, is part of the 2018 Evidence to Action: Research to Address Illegal Wildlife Trade event programme, organised by five of the UK’s most active IWT research institutions, to support the London 2018 IWT Conference.

Making humanitarian response more flexible: Challenges and questions - Obrecht, Alice; Bourne, S. (ALNAP/ODI, 2018)

Doing Development Differently in the Global South - Workshop Report - CARE (CARE and British Council, 2018)

USAID ADS 201 - Program Cycle Operational Policy (Update 10/29/2018) - USAID (USAID, 2018)

Review of Selected DFAT Facilities: Independent Consultant Report to DFAT, Key Findings - Pieper, Lynn (DFAT, 2018)
For the purposes of this report, a facility is defined as an aid delivery mechanism that provides flexible (adaptive and responsive) services managed in an integrated way. Objectives (or endof-facility outcomes) are specified, but the pathways to deliver them are left unspecified. The facility is a highly relevant model for delivering Australian aid effectively. Achievement of the Sustainable Development Goals depends on flexible approaches that work across sectors and that integrate significant cross-cutting themes such as gender equality and social inclusion. Efficient DFAT management of a $4 billion aid program requires a shift to fewer and larger initiatives, to make best use of limited internal management resources while still enabling policy and program choices that can have real impact. Facilities and other flexible delivery mechanisms offer significant potential for better development results. They can: enable collaborative and responsive partnership approaches to gain traction; allow activities to experiment and adapt based on progress, demand and contextual changes; and provide the opportunity for outcome-focused coherence across sectors, enabling the whole to be more than the sum of the parts. Facilities are not new, but they are different today. Facilities have existed since at least the mid-1990s. What is new is that some facilities today are very large; and the flexibility they enable is increasingly and consciously being used to strengthen links between the technical and the political, for more effective development results. This is a positive trend, but it adds enormously to their complexity and visibility, creates new risks, and has resulted in role confusion (especially in early years of implementation) between DFAT and its contractors.

Bringing Participation into Complexity-Aware MEL: What is the evidence? - Apgar, Marina; Higdon, Grace Lyn (2018)

What can the Thinking and Working Politically community learn from peace and conflict mediation? - Douglas, Alex (From Poverty to Power, 2018)
Wily aid practitioners have long understood the importance of adapting their programs to the political environment, and even use their activities to push politics in a progressive direction. But this magic was spun secretly, hidden behind logframes and results frameworks. Only recently has a range of programs been permitted to escape the dead hand of technocracy. But there was one corner of the development and humanitarian world that never needed to shroud its political ambitions; those of us working on resolving violent conflicts. Donors have always understood our work could never be disembodied from politics. This field included elements of the UN, regional organisations, and NGOs, such as the one I work for: the Centre for Humanitarian Dialogue. With a new focus on development being enabled by a series of ‘deals’ between different actors, it seems timely to examine the strategies used to reach peace agreements and whether they contain broader lessons for TWP/DDD/Adaptive Management.

Strengthening Advocacy and Civic Engagemetn in Nigeria - Chemonics (Chemonics International, 2018)

The Whistler principles to accelerate innovation for development impact - G7 (G7, 2018)
The Whistler principles to accelerate innovation for development impact : 2018 G7 Summit – Canada 2018 G7 Presidency – Charlevoix, Quebec

Simplexity² or: How I Learned to Stop Worrying and Love Complexity in Development - Prieto Martin, Pedr (Complexity and Development Seminar Series, 2018)
This seminar is the fifth in a series that aims to share cutting edge thinking and research being done at IDS and the University of Sussex around how we practically capture and account for complexity across a variety of sustainable development contexts. Join us for a fascinating trip from Athens to Xiaogang where, assisted by Steve Jobs, Sun Tzu and Aristotle, and with the help of a series of memorable diagrams, we attempt to alchemise development’s complexity into… a simple living tree. The seminar aims to integrate into an accessible narrative notions from various disciplines related to complexity science –including psychology, philosophy, organisational development and software engineering– as a way to articulate essential complexity concepts. Insights emerging from our cluster’s research on Adaptive Management and on the use of Frontier Technologies for development are linked with ideas presented by Prof. Chambers, Burns, Scoones and Ang in the previous seminars, to explore what complexity means in practice for development professionals and how we can discern and handle it at best. About the Speaker Pedro Prieto Martín is a software engineer turned trans-disciplinary social scientist. Pedro’s academic background includes degrees in Computer Science, Business Administration, Philosophy, and Sociology from different Spanish universities. After working for years at Hewlett-Packard in Germany as the Technical Lead of a development team, he moved to Latin America, where for years he researched the application of ICT to improve local governance and promote social change. Before joining the Digital and Technology cluster he supported and researched, at the local level, the social mobilisation processes that resulted from the “indignados” movement in Spain and their use of ICT. At IDS, Pedro has investigated the drivers of adaptiveness in accountability interventions, as part of MAVC. He now coordinates the learning component of DFID’s “Frontier Technologies Livestreaming (FTL)” programme, which has been recently awarded UK’s Civil Service Award for Innovation. FTL supports DFID country offices to experiment with the use of emerging technologies to address development challenges.

Scaling Up Inclusive Approaches for Marginalised and Vulnerable People - Carter, Becky; Joshi, Anu; Remme, Michelle (2018)
This rapid review summarises the evidence on how to scale up inclusive approaches to complex social change. It looks at how to design scalable inclusive change interventions, as well as how to plan and manage the scale-up process. Focusing on interventions with the aim of reaching the most marginalised and transform social norms, it covers programmes aiming to deliver inclusive outcomes for women and girls (with a particular focus on preventing violence against women and girls) and persons with disabilities. To date, many interventions seeking to change harmful gender and disability norms have been implemented as small-scale projects. There are limited experiences of scale-up and fewer evaluations of these experiences. However, there are some documented case studies as well as emerging analysis that draw out lessons learned. From this evidence base, this rapid desk review identifies eight critical issues commonly highlighted as important considerations when scaling up inclusive change interventions: 1. Opportunities for systemic approach, including integrating political and community-level scale-up, and coordinating across multiple sectors and stakeholders 2. Political support for scale-up 3. Strategic choices: balancing reach, speed, cost, quality, equity, and sustainability 4. Catalysing change: tipping points, diffusion effects, and local champions 5. Locally grounded, participatory, and adaptive approaches 6. Long-term approaches with funding models to match 7. Cost-effective and financially feasible scale-up strategies 8. Measuring impact and sustainability.